2016
DOI: 10.1371/journal.pone.0145921
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Triphala on Dermal Fibroblasts and Human Keratinocytes

Abstract: Human skin is body’s vital organ constantly exposed to abiotic oxidative stress. This can have deleterious effects on skin such as darkening, skin damage, and aging. Plant-derived products having skin-protective effects are well-known traditionally. Triphala, a formulation of three fruit products, is one of the most important rasayana drugs used in Ayurveda. Several skin care products based on Triphala are available that claim its protective effects on facial skin. However, the skin protective effects of Triph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 68 publications
(73 reference statements)
0
19
0
Order By: Relevance
“…Increases expression of SOD-2 in HDF or HaCaT skin cells. [49] Restores CAT, SOD, GST, GPx and GSH in bromobenzene treated rat kidney. [50] Prevents peroxidative damage by increasing GSH and GST and decreasing LPO in DMH treated mouse liver.…”
Section: Ros Scavengingmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases expression of SOD-2 in HDF or HaCaT skin cells. [49] Restores CAT, SOD, GST, GPx and GSH in bromobenzene treated rat kidney. [50] Prevents peroxidative damage by increasing GSH and GST and decreasing LPO in DMH treated mouse liver.…”
Section: Ros Scavengingmentioning
confidence: 99%
“…Triphala extract also inhibits H 2 O 2 -induced RBC haemolysis, nitric oxide production and shows high reducing power activity. As H 2 O 2 induces cellular damage, it has been shown that pretreatment with Triphala rescues the human dermal fibroblast from H 2 O 2 -induced damage, inhibits cellular senescence, and protects DNA from damage [49]. Triphala has been found to increase glutathione (GSH) and decrease malondialdehyde levels in enucleated rat lenses.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…[33][34][35][36][37] The scientic validation of the pharmaceutical properties of these Ayurvedic formulations is beginning to emerge. [33][34][35][36][37] Triphala, an Ayurvedic formulation containing naturally occurring polyphenols, is known to possess a wide range of medicinal properties such as free radical scavenging, antioxidant, anti-inammatory, antimutagenic, antistress, hypoglycaemic and radioprotective which have been recently reviewed. 38 Some of these properties of Triphala are believed to be due to its polyphenolic constituents.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, RBE increased the filaggrin and involucrin content in HaCaT cells, the two proteins playing a crucial role in skin-barrier function. Earlier reports have shown that natural products increase the involucrin and filaggrin content in HaCaT cells, thereby maintaining skin barrier function (Satyabrata et al, 2016;Varma et al, 2016). In dermal pathophysiological course, AQP-3 can transport water and glycerol to epidermis, so AQP-3 is significant to epidermal barrier and water retention (Slominski et al, 2014).…”
Section: Discussionmentioning
confidence: 99%